REVIEW ARTIKEL: KARAKTERISTIK DAN PERANAN ENZIM LIPASE PADA PRODUKSI DIACYGLYCEROL (DAG) DARI VIRGIN COCONUT OIL (VCO) - Emilisia Fatimah (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2021)
Lipase enzyme is an acyl hydrolase that functions in the digestion and processing of fat. Lipase enzyme have activities that can hydrolyze various fats and oils, each one unit per mL (U/mL) of lipase enzyme activity can release 1 µmol of free fatty acids per minute. Lipase enzyme activity at optimum conditions obtained from measurements of enzymatic activity at modification of temperature and pH. Lipase enzyme can be found in plants, animals, and microorganisms. Coconut (Cocos nucifera L.) is a plant that produces lipase enzymes which can produce Virgin Coconut Oil (VCO). VCO can be converted into diacylglicerol (DAG) by hydrolysis or trans-esterification using chemical or enzymatic methods. DAG is a type of healthy oil that can reduce the content of Low Density Lipoprotein (LDL), triglycerides (TG) and become a plasminogen inhibitor. Key words: Lipase, Diacyglycerol (DAG), Virgin Coconut Oil (VCO)